Pengaruh Efikasi Diri dan Disposisi Matematis Terhadap Kemampuan Penalaran Matematis Peserta Didik Sekolah Dasar - Gulo, Prima Sari; Harefa, Noniat Citra; Gulo, Indah Restuti; Lahagu, Sinta Novita Sari; Waruwu, Sepni Putri Indartin; Lase, Grace Sri Leony; Rispen Elfandi Lase; Bugis, Windy Syafriah; Harefa, Edward (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze the relationship between self-efficacy and mathematical disposition to students' mathematical reasoning ability. The research method used is a quantitative research method. The sample of this study is 65 students, who were selected using a simple random sampling technique. The data collection technique is using a questionnaire. The data analysis used included normality test, multicollinearity test and heteroscedasticity test followed by associative hypothesis test and multiple linear regression. The results in the study showed that there was no multicollinearity and heteroscedasticity in the data. In the results of the associative hypothesis test, the variables of self-efficacy and mathematical disposition influenced the variable of mathematical reasoning ability by 78.10 percent. The influence of self-efficacy and mathematical disposition itself has a positive influence on the mathematical reasoning ability of students in elementary school